Pengaruh Financial Knowledge, Financial Technology dan Social Environment Terhadap Perilaku Keuangan Generasi Z di Kota Pekanbaru - Hikmah, Nadatul; Nurani, Ratna (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Financial behavior is a crucial aspect, especially for young generations facing economic challenges and technological advancements. This study aims to analyze the influence of financial knowledge, financial technology, and social environment on the financial behavior of Generation Z in Pekanbaru City. Using a quantitative approach and 150 respondents selected through the G*Power application, data were collected via an online Likert-scale questionnaire and analyzed using SmartPLS 4.0. The results show that all three independent variables have a positive and significant effect on financial behavior, with an R² value of 0.693. This means that 69.3% of the variation in financial behavior can be explained by this model. These findings highlight the importance of improving financial literacy, utilizing financial technology, and fostering a supportive social environment in shaping healthy financial behavior. The implication is the need for educational interventions and policies that promote inclusive access to financial information for young people.